Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique